Polymerization Domain Translated from 0.9 kb Gene Fragment of DNA Polymerase I from a Thermo-Halophilic PLS A Strain - Teuku Mohamad Iqbalsyah; Muhammad A Velayati; Hira Helwati; Febriani Febriani (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
The search for novel DNA Polymerases I, with higher fidelity and better polymerization rate, is essential to improve the Polymerase Chain Reaction method. A thermo-halophilic bacterium has been isolated from an undersea hot spring, dubbed Pria Laot Sabang (PLS) A strain. The 0.9 kb DNA Polymerase I gene fragments from the isolate were amplified, sequenced, and identified. The fragments were part of the polymerization domain of the enzyme. Homological analysis of the gene sequence showed that the PLS A strain was closely related to Bacillus caldolyticusstrain XM. However, Swissprot structural analysis reveals that PLS A strain had high homology to Geobacillus stearathermophilus. Full sequence analysis is still needed to identify the species and evaluate the intact enzyme structure.